Maria Bogucka. A Woman Writing on the History of Women - Jakuboszczak, Agnieszka (Acta Poloniae Historica, 2023)
Issues related to women’s history and feminism occupied a central place in Maria Bogucka’s research. It is not without significance that her work in this area corresponds to the dynamic development of research on the history of women in Western Europe and the United States. Women, often overlooked in historical research, represented important heroines not only as queens or saints, but also as characters whose group portrait was essentially worth recreating. Maria Bogucka looked to address women’s (and feminist) issues in biographies, monographs, articles and essays. To this end, she introduced the findings of foreign researchers into Polish historiography, and emphasised the specificity of the situation of women in Poland over the centuries.